FRAUD DIAMOND TERHADAP FINANCIAL STATEMENT FRAUD - Al Farizi, Zulham; Tarmizi, Tashadi; Andriana, Susan (Balance : Jurnal Akuntansi dan Bisnis, 2020)
This study aims to examine the effect of diamond fraud on financial statement fraud: an empirical study in the west kalimantan province, both partially and simultaneously. Fraud can occur in every country with different types and frequencies, because there are still potential risks of corruption in the political system that hasn’t changee. In addition, there are indications of suspicious relation between politicians and business people who explain that bribery and corruption are still present in the indonesian political system. Fraud Diamond’s research results on the financial statement fraud: empirical study in west kalimantan, shows that partially external presure and opportunity affect the financial statement farud, while rationalization and capability doesn’t affect the financial statement fraud. In addition, simultaneously external presure, rationalization, opportunity, and capability affect the  financial statement fraud of 86,4%, while the remaining 13,6% is influence by other variables not examine in this study